Clinical value of spectral CT in diagnosis of negative gallstones and common bile duct stones. - Li, Huanguo; He, Dong; Lao, Qun; Chen, Xingcan; Liu, Miao; Yin, Bingxin; Zhao, Kaiyu; Wang, Rui; Chen, Longxia (Abdominal Imaging, 2015)
Objective: To investigate the clinical value of spectral CT in diagnosis of negative gallstones and common bile duct stones primarily.Methods: All patients diagnosed with negative biliary stones were analyzed and examined by spectral CT scanner retrospectively. Based on acquired raw imaging data, image series were reconstructed as described below: the optimal contrast-to-noise ratio monochromatic energy images, calcium- and fat- based material decomposition images and spectral curve images. All these imaging series were analyzed quantitatively and qualitatively.Results: The contrast between negative stones and adjacent bile was 6.87 ± 5.48 HU on hybrid energy CT images and 47.30 ± 24.05 HU on optimal monochromatic energy CT images. The mean concentration of calcium in bile and negative stones was 19.36 ± 5.12 and 3.88 ± 6.60 mg/mL, and the fat in bile and negative stones was 998.48 ± 11.79 and 1035.68 ± 15.36 mg/mL. Effective atomic number Z of negative stones (6.60 ± 0.45) was lower than that of bile (7.65 ± 0.13). The slopes of the spectral curves for negative stones were k 90-40KeV = 1.43 ± 0.63 and k 140-90KeV = 0.19 ± 0.08, and for bile, they were k 90-40KeV = -0.27 ± 0.09 and k 140-90KeV = -0.04 ± 0.01. The same stone showed different densities in different imaging groups. The positive rate of conventional CT images was lower than that of other imaging groups.Conclusion: Spectral CT has a high diagnostic value for negative gallstones or bile duct stones, and material decomposition CT images and spectral curves can make an accurate diagnosis.